Identification of Misconceptions in Jotform-Based Physics During The Covid-19 Pandemic - Yulita Safitri; Dewi Dewantara; Eko Susilowati (Universitas Muhammadiyah Purworejo, 2022)
This research aims to explain the level of misconception experienced by students identified by the Four-Tier Diagnostic Test based on the JotForm for each subconcept of heat and heat transfer. The subject of this research were students of class XI MIPA 1 and MIPA 2 with a total of 78 students as respondents. The research method uses a qualitative descriptive research type. The research instrument is in the form Four-Tier Diagnostic Test questions using JotForm. Data collection techniques through shared links are then carried out by respondents with the help of Google Meet to monitor respondents and through interviews. The results of data acquisition are interpreted using an interpretation table and calculate the percentage of each category. Based on the results of the overall data acquisition, it shows that students in class one experience misconceptions in the moderate level category, while in the class other in the law level category. The highest percentage of misconceptions for each subconcept of heat and heat transfer experienced by students is in the concept of temperature. The data from this research can be used as a source of information regarding misconceptions that occur in heat material and heat transfer that need to be addressed in order to reduce the potential for misconceptions and efforts to overcome them.